Increasing Sixth Grade Students' Engagement in Literacy Learning - Laura Jordan; Cher Hendricks (Networks: An Online Journal for Teacher Research, 2002)
This study is the result of collaboration between a classroom teacher (Laura Jordan) and a university professor (Cher Hendricks). Laura, who completed the initial literature review and collected and analyzed data collected in the field, writes the study in first person. Cher provided assistance in developing the action plan, developing the literature review, and preparing the written study.